Pengaruh E-Website Quality dan E-Service Quality terhadap E-Repurchase Intention melalui E-Trust (Studi pada Konsumen produk fashion Lazada Mahasiswa Universitas Diponegoro) - Damas Ade Priambodo; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2020)
The rapid development of e-commerce makes businessman vying to build a business empire through e-commerce. To be able to compete e-commerce must improve the quality of the website, service quality and level of trust so that it gets market share and valuation. The purpose of this study was to determine the effect of e-website quality and e-service quality on e-repurchase intention through e-trust in consumers of Lazada fashion products of Diponegoro University students. This type of research is explanatory research with data collection techniques through Google forms. The sample of this study was 100 consumers of Lazada fashion products from Diponegoro University students. The analysis technique used is quantitative analysis with the help of the SmartPLS (Part Least Square) application version 3.2.9. The results showed a positive and significant effect on e-website quality on e-trust, e-service quality on e-trust, and e-trust on e-repurchase intention. The indirect test results show that there is a positive and significant influence of e-website quality on e-repurchase intention through e-trust and e-service quality on e-repurchase intention through e-trust.Perkembangan e-commerce yang semakin pesat membuat pebisnis berlomba-lomba untuk membangun kerajaan bisnis melalui e-commerce. Agar mampu bersaing e-commerce harus meningkatkan kualitas website, kualitas layanan dan tingkat kepercayaan sehingga mendapat pangsa pasar dan valuasi. Tujuan penelitian ini adalah untuk mengetahui pengaruh e-website quality dan e-service quality terhadap e-repurchase intention melalui e-trust pada konsumen produk fashion Lazada mahasiswa Universitas Diponegoro. Tipe penelitian ini adalah explanatory research dengan teknik pengumpulan data melalui google form. Sampel dari penelitian ini adalah 100 konsumen produk fashion Lazada mahasiswa Universitas Diponegoro. Teknik analisis yang digunakan adalah analisis kuantitatif dengan bantuan aplikasi SmartPLS (Part Least Square) versi 3.2.9. Hasil penelitian menunjukkan adanya pengaruh positif dan signifikan pada e-website quality terhadap e-trust, e-service quality terhadap e-trust, dan e-trust terhadap e-repurchase intention. Hasil uji pengaruh tidak langsung menunjukkan adanya pengaruh positif dan signifikan e-website quality terhadap e-repurchase intention melalui e-trust serta e-service quality terhadap e-repurchase intention melalui e-trust.